A reliability analysis method using binary decision diagrams in phased mission planning - Prescott, Darren; Remenyte-Prescott, Rasa; Reed, Sean; Andrews, John; Downes, C.G. (Sage, 2009)
The use of autonomous systems is becoming increasingly common in many fields. A significant example of this is the ambition to deploy UAVs (unmanned aerial vehicles) for both civil and military applications. In order for autonomous systems such as these to operate effectively they must be capable of making decisions regarding the appropriate future course of their mission responding to changes in circumstance in as short a time as possible. The systems will typically perform phased missions and, due to the uncertain nature of the environments in which the systems operate, the mission objectives may be subject to change at short notice. The ability to evaluate the different possible mission configurations is crucial in making the right decision about the mission tasks that should be performed in order to give the highest possible probability of mission success.